2010
DOI: 10.1103/physrevd.81.106007
|View full text |Cite
|
Sign up to set email alerts
|

Holographic superconductors with various condensates in Einstein-Gauss-Bonnet gravity

Abstract: We study holographic superconductors in Einstein-Gauss-Bonnet gravity. We consider two particular backgrounds: a d-dimensional Gauss-Bonnet-AdS black hole and a Gauss-Bonnet-AdS soliton.We discuss in detail the effects that the mass of the scalar field, the Gauss-Bonnet coupling and the dimensionality of the AdS space have on the condensation formation and conductivity. We also study the ratio ωg/Tc for various masses of the scalar field and Gauss-Bonnet couplings.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

33
211
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 176 publications
(248 citation statements)
references
References 39 publications
33
211
2
2
Order By: Relevance
“…Recently, an s-wave holographic dual model with Weyl corrections has been constructed in order to explore the effects beyond the large N limit on the holographic superconductor [23]. It is shown that, in strong contrast to the higher curvature corrections [10][11][12], the higher Weyl corrections make it easier for the condensation to form and change the expected relation in the gap frequency. Generalizing the investigation on the holographic superconductor model in the Stückelberg mechanism, the authors of Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an s-wave holographic dual model with Weyl corrections has been constructed in order to explore the effects beyond the large N limit on the holographic superconductor [23]. It is shown that, in strong contrast to the higher curvature corrections [10][11][12], the higher Weyl corrections make it easier for the condensation to form and change the expected relation in the gap frequency. Generalizing the investigation on the holographic superconductor model in the Stückelberg mechanism, the authors of Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand the influences of the 1/N or 1/λ (λ is the 't Hooft coupling) corrections on the holographic dual models, there have been a lot of works studying the holographic superconductors with the higher derivative correction related to the gravity [10][11][12] and the gauge field [13][14][15][16][17][18][19][20][21][22]. Recently, an s-wave holographic dual model with Weyl corrections has been constructed in order to explore the effects beyond the large N limit on the holographic superconductor [23].…”
Section: Introductionmentioning
confidence: 99%
“…The AdS/CFT duality is a powerful tool for investigating strongly coupled gauge theories, the application might offer new insight into the study of strongly interacting condensed matter systems where the perturbational methods are no longer available. Therefore, much attention has been given to the studies of the AdS/CFT duality to condensed matter physics and in particular to superconductivity recently [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In these studies most of the holographically dual descriptions for a superconductor are based on a model that a simple Einstein-Maxwell theory coupled to a charged scalar.…”
Section: Introductionmentioning
confidence: 99%
“…Applications in high energy physics have been particularly important [10], [11]. Higher order corrections to the gravity counterpart have been often used, but a general discussion is still missing [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%